Divine and demonic imagery at Tor de'Specchi, 1400-1500 : religious women and art in fifteenth-century Rome - Scanlan, Suzanne M. (Visual and material culture, 1300-1700., 2018)
In the fifteenth century, the Oblates of Santa Francesca Romana, a fledgling community of religious women in Rome, commissioned an impressive array of artwork for their newly acquired living quarters, the Tor de'Specchi. The imagery focused overwhelmingly on the sensual, corporeal nature of contemporary spirituality, populating the walls of the monastery with a highly naturalistic assortment of earthly, divine, and demonic figures. This book draws on art history, anthropology, and gender studies to explore the disciplinary and didactic role of the images, as well as their relationship to important papal projects at the Vatican.